Age, landscape, and arrival date explain ranging behavior of wintering red kites in southwest Europe. Issue 1 (30th December 2021) - Panter, Connor T.; Literák, Ivan; Raab, Rainer; Tolhurst, Bryony A.; White, Rachel L.
Abstract: Understanding intrinsic and extrinsic influences of movement behavior in migratory species, with the potential to recommend management actions for species of conservation concern, requires data from across the species' range. For some raptor species, such as the red kite ( Milvus milvus ; kite), existing data focus on breeding populations or movements en route to wintering areas without considering movements within the wintering areas. Here, we contribute to filling this knowledge gap by investigating landscape‐level associations of kites in their southwestern European winter ranges between 2015 and 2020. We also explore aspects of the migration process in terms of geographical patterns in the location of over‐wintering grounds, including time spent and distances traveled within them. We predicted that space use in over‐wintering areas would be linked to the proportional amount of open, lowland, or urban land cover they contain at the landscape level. Specifically, we tested whether winter range sizes (95% kernel density estimator [KDE] home ranges and 50% KDE core areas) would be smaller in areas with greater proportional open and urban land cover within kite ranges. Controlling for the effects of age and sex, we compared results in 3 over‐wintering regions: the Iberian Peninsula, Italy, and the Pyrenean region of southern France. We tracked 36 kites by global positioning system‐global system for mobile communications (GPS‐GSM) telemetry over 70 individual winters between 2015 and 2020. Kites wintering in the Pyrenees had larger home ranges and core areas but moved less than those wintering in Italy and the Iberian Peninsula. As predicted, ranges were smaller in areas with greater proportional open and lowland land cover; however, there was no effect of urban areas. Older kites that arrived late to the wintering areas had larger home ranges than those that arrived early or on time. During the study 20 kites died or the transmitter malfunctioned. Six of 13 confirmed deaths were due to anthropogenic activity; 5 kites were poisoned. Our results confirm that land use and elevation are key influences of kite space use in southwestern European over‐wintering populations, but additional demographic intrinsic factors also affect ranging parameters. These data indicate that over‐winter conservation action for kites, for example supplementary feeding with livestock carrion, should focus on open lowland landscapes throughout the species' winter range. Abstract : We fill knowledge gaps on ranging and survival for 36 red kites during winter. Older kites arriving late to over‐wintering grounds ranged farther, and open, lowland landscapes were key predictors of winter space use.